Dynamic modeling and fuzzy logic control of vibrations of a railway vehicle for different track irregularities - Sezer, Semih; Atalay, Ali Erdem (ELSEVIER, 2011)
Safe and comfortable transportation of passengers and goods on railways can be achieved by solving the vibration problem. In this study, the dynamic modeling of the full railway vehicle is used to perform vibration analysis in order to observe displacements and accelerations. The full railway vehicle model consists of 54 degrees of freedom which are defined by differential equations. Additionally, wheel-rail contact problem (i.e. creepage factors and hertzian spring stiffness of rails) is analyzed by finite element method. Dynamic modeling and vibration analysis are carried out using Matlab-Simulink software. Using the developed model, the car body vibrations, caused by a lateral and two vertical sinusoidal track irregularities, are controlled by fuzzy logic controllers placed between the car body and bogies. The fuzzy logic algorithm herein is used for realizing the active control of car body vibrations. The simulations of vibration analysis are obtained in time and frequency domains and compared with passive controlled status. The robustness of the designed controller is verified by simulations, carried out for the cases of car body mass variations. The results show the effectiveness of the proposed algorithm. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Railway vehicle dynamics; Dynamic modeling; Active control of vehicle vibrations; Simulation of vibrations; NEURAL-NETWORK CONTROL; SYSTEM; SIMULATION; Computer Science